Bersama Masyarakat, Membangun Pendidikan Unggul: Peran Madrasah Ibtidaiyah dalam Mendorong Transformasi Sosial - Septya, Jelita Dwi; Ziliwu, Siskawati; Lubis, Rodiatul Hasanah; Hasanah, Sa’idatul; Ritonga, Adelia Priscila; Safitri, Lusi; Uswah, Fadhilah (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This research aims to describe the role of Madrasah Ibtidaiyah as a social change agent through innovation in three main areas: curriculum, teaching methods, and community involvement. This research not only focuses on academic aspects, but also highlights the formation of character, religious values, and the development of relevant practical skills. This holistic approach is expected to make a significant contribution in strengthening the role of Madrasah Ibtidaiyah as an educational institution capable of shaping quality and competitive generations. The research results show that through community service activities at PGMI 6 UINSU, it can be concluded that education in Madrasah Ibtidaiyah has a positive impact on shaping students' character and reducing educational inequality. Madrasah, in addition to being a place for formal learning, also plays a role as a center for the formation of moral and social values for its students.